The summer wind - Monroe, Mary Alice (Monroe, Mary Alice. Lowcountry summer trilogy., 2014)
"This heartwarming women's fiction series from beloved New York Times bestselling author Mary Alice Monroe centers on Marietta Colson Muir, a dowager of Charleston society who has retired to her historic summer home on Sullivan's Island called Conquest, and her three granddaughters Carson, Eudora, and Harper. It's summer once again on idyllic Sullivan's Island, but Eudora, or Dora as she's affectionately called by her family, is feeling anything but perfect. With a perpetually withdrawn son and an impending divorce, the pressure is just too much to handle, and Dora cracks, suffering what the doctors are calling 'Broken Heart' syndrome. Mamaw, Lucille, Harper, and Carson all rally around Dora to support her and nurse her back to health--however, it seems Dora isn't the only one falling apart this summer. Between Lucille's health scare and an unexpected surprise that has Carson reconsidering her life's direction, it looks like all the women of Sullivan's Island could use some TLC. When Sullivan's is hit with a tropical storm, it will be up to the three sisters to band together and weather the tempest together--both the one outside their windows, and the raging sea of emotions within each one of them" --